The Secrets of Acinetobacter Secretion. Issue 7 (July 2017) - Weber, Brent S.; Kinsella, Rachel L.; Harding, Christian M.; Feldman, Mario F.
Abstract : Infections caused by the bacterial pathogen Acinetobacter baumannii are a mounting concern for healthcare practitioners as widespread antibiotic resistance continues to limit therapeutic treatment options. The biological processes used by A. baumannii to cause disease are not well defined, but recent research has indicated that secreted proteins may play a major role. A variety of mechanisms have now been shown to contribute to protein secretion by A. baumannii and other pathogenic species of Acinetobacter, including a type II secretion system (T2SS), a type VI secretion system (T6SS), autotransporter, and outer membrane vesicles (OMVs). In this review, we summarize the current knowledge of secretion systems in Acinetobacter species, and highlight their unique aspects that contribute to the pathogenicity and persistence of these emerging pathogens. Trends: Known mechanisms for protein secretion by A. baumannii include a type II secretion system (T2SS), a type VI secretion system (T6SS), autotransporter, and outer membrane vesicles (OMVs). The T2SS secretes several effector proteins, including lipases and proteases, and is required for pathogenesis. A new family of T2SS effector chaperones that appear to be widespread among Gram-negative pathogens has been identified. In some strains of A. baumannii, T6SS is repressed by a plasmid that carries antibiotic-resistance genes, and this plasmid can be spontaneously lost, leading to T6SS activation with loss of resistance. A. baumannii T6SS assembly requires a dedicated peptidoglycanase named TagX. A. baumannii OMVs contain virulence factors and may be useful as vaccines.